2013
DOI: 10.1186/1471-2474-14-189
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative technique to create a femoral tunnel at the averaged center of the anteromedial bundle attachment in anatomic double-bundle anterior cruciate ligament reconstruction

Abstract: BackgroundIn the anatomic double-bundle ACL reconstruction, 2 femoral tunnel positions are particularly critical to obtain better clinical results. Recently, a few studies have reported quantitative identification methods for posterolateral (PL) bundle reconstruction. Concerning anteromedial (AM) bundle reconstruction, however, no quantitative clinically available methods to insert a guide wire at the center of the direct attachment of the AM mid-substance fibers have been reported to date.MethodsFirst, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“… 14 It was originally described for radiographies, but is also utilized in 3D CT scan evaluation. 2 , 10 , 11 , 14 , 15 In rendered and cropped 3D CT scans, high levels of intra- and inter-observer reliability were demonstrated 14 , 15 , 17 for this quadrant method technique, as the present study demonstrated.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“… 14 It was originally described for radiographies, but is also utilized in 3D CT scan evaluation. 2 , 10 , 11 , 14 , 15 In rendered and cropped 3D CT scans, high levels of intra- and inter-observer reliability were demonstrated 14 , 15 , 17 for this quadrant method technique, as the present study demonstrated.…”
Section: Discussionsupporting
confidence: 74%
“…The same simulated central ACL position was loaded in the transparent sagittal view, as described before, and the quadrant method of Bernard et al 12 was applied in the picture obtained, as described by Lertwanich et al 15 and Kai et al 10 In 3D CT scans. A line connecting the most anterior and posterior edge of the intercondylar roof was the reference for Blumensaat line.…”
Section: Methodsmentioning
confidence: 99%
“…We determined an appropriate guide wire location using the previously reported fluoroscopic method. 23,48 After the guide wire was inserted, a femoral tunnel was gently drilled by use of a cannulated drill, penetrating the remnant tissue.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…The details of the anatomic procedure have been previously described ( Figure 2 ). 14 , 37 , 38 In the double-bundle procedure, the AM graft diameter ranged from 6 to 6.5 mm (mean ± SD, 6.3 ± 0.3 mm), and the PL graft diameter ranged from 5.5 to 6 mm (mean ± SD, 5.8 ± 0.2 mm).…”
Section: Methodsmentioning
confidence: 99%